WEST SUMATRA’S RETAIL POLICIES ON THE PERSPECTIVE OF COMPETITION AND ISLAMIC LAW - Ulfanora, Ulfanora; Almaududi, Almaududi (Fakultas Hukum, Universitas Diponegoro, 2024)
This study examines the legal framework regulating retail markets in Indonesia, focusing on balancing modern retail growth with the protection of micro, small, and medium enterprises (MSMEs). The introduction highlights the rapid expansion of modern retail chains and their impact on traditional markets, emphasizing West Sumatra’s unique approach of limiting the entry of major retail chains to support local businesses. However, this policy lacks clear written regulations, creating legal and operational uncertainties. Using a doctrinal legal research methodology, the study analyzes statutory laws, legal doctrines, and secondary sources. Key legal instruments include the Law on Prohibition of Monopolistic Practices and Unfair Business Competition, the Job Creation Law, and Regional Regulations on Fostering and Empowering People's Markets. The qualitative analysis focuses on identifying inconsistencies, gaps, and the synchronization of these regulations. The findings reveal the absence of explicit legal provisions supporting local governments’ restrictions on modern retail, despite their efforts to protect traditional markets. The study underscores the need for comprehensive and clear legal frameworks to ensure fair competition, safeguard MSMEs, and align with national socio-economic goals. Recommendations include regulatory reforms to address ambiguities and support sustainable retail market policies